Innovations in irrigation financing: tapping domestic financial markets in India - Raju, K. Vengama; Gulati, Ashok; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2003)
Financing for water projects, especially for irrigation, has been moving towards collapse in recent years due to declining donor and government funding. Some Indian states have undertaken innovative institutional reforms by setting up financially autonomous corporations to mobilise required funds from the domestic bond market. This analysis of the performance of one such corporation, Karnataka's Krishna Bhagya Jal Nigam Limited, indicates that although adequate funds were mobilised, and physical works are on schedule, the new institution did not attempt to enhance overall irrigation performance and to move towards financial sustainability of the irrigation project. This paper describes the background of this institution, its achievements, inadequacies and potential of the innovative efforts made in irrigation financing reforms. -- Authors' Abstract